A responsabilidade do empregador na degradação do meio ambiente do trabalho e suas conseqüências jurídicas no âmbito do direito do trabalho - Belfort, Fernando José Cunha (2008)
The main goal of this thesis is to show that there is no plausible reason for the different treatments given in the assessment of the damage caused to the environment. Indeed, if the deterioration is against the environment we aplly the "teoria da culpa objetiva" (objective damage responsability theory). However, when it comes to accidents suffered by the employee, two situations have to be considered: if the damage caused to the employee derives from the degradation of the environment of work - artificial environment we should consider the" teoria da culpa objetiva" (objective damage responsability theory); But, on the other hand, if the misfortune is not caused by the environmental degradation, such as a typical accident, even though doctrine and jurisprudence may consider the above theory, we shall demonstrate it's unconstitutional interpretation, as seen that this was not the intention of the legislature when implemented the " teoria da culpa subjetiva ou aquiliana" (subjective damage responsability theory). This thesis is solidly supported by the doctrine of both objective and subjective theories. Over all, the environment is a right that belongs to the so-called fundamental rights of third generation, inserted in our constitution. We review the environment of work, its concept , general principles and without altering the essence of them, we rename some principles of our labour environment relating to the ones being used already. We talk about accidents at work, its origin, its causes and consequences, legislation, its concept, theories and responsibilities. We approach the moral responsability (damage), its concept, the comparative law and the historical development in Brazil. Also, the responsibility of environmental damage in its various aspects, features and the rule of our "responsabilidade objetiva" (objective damage responsability theory) in environmental damage, to finally complete this paper showing how to repair the damage in accidents at work. An extensive bibliography has been consulted, including research related to the theme at the Federal Supreme Court and the Senate